The cytologic analysis of aqueous humor in eyes with uveitis - Özdamar Erol, Yasemin; Kazancı, Burcu; Kaya, Pınar; Sabuncuoğlu, Bizden; Bayrak, Gözde; Karabacak, Rukiye; Özdal, Pınar (Acta Medica, 2023)
Purpose: The purpose of this study was to evaluate the cytologic analysis of aqueous humor (AH) of the eyes with Fuchs uveitis (FU) and idiopathic anterior uveitis (IAU). Methods: AH of 25 uveitic eyes (12 FU and 13 IAU) were evaluated cytologically. The samples of the anterior chamber were taken before cataract surgery. Aqueous fluid samples were evaluated by applying a Giemsa stain. Results: The 12 patients with FU and 13 patients with IAU were included in this study. In AH, the number of lymphocytes was similar in eyes with FU and IAU (the number of lymphocytes: min:1 and max:7). The acellular amorphous structures were detected in eyes with FU, and the same finding was not observed in the eyes with IAU. In addition, any pigmented cells or accumulation were not detected in any of the eyes. Conclusion: The acellular amorphous structures were the remarkable finding of this study. It has been considered that amorphous structures in the AH of the eyes with FU could be related to chronic, low-grade anterior chamber inflammation and responsible for several complications of uveitis. FU is a uveitic entity with mysterious findings that await clarifications in its etiopathogenesis.